Governance Of An Integrated Qur’anic Literacy Program Based On Religious Habituation In Shaping Madrasah Ibtidaiyah Graduate Profiles - Siti Nur Amini; Khoirotul Muslimah (STAI Al-Mas'udiyah, 2025)
The development of Qur’anic literacy in Islamic elementary education plays a crucial role in shaping students’ religious competence and character. However, existing studies on Baca Tulis Al-Qur’an (BTQ) programs predominantly emphasize instructional methods and technical skill improvement, while limited attention has been given to how program governance integrates religious habituation in forming graduate profiles. This gap indicates a discrepancy between the intended outcomes of Islamic education and the managerial practices implemented in schools. This study aims to analyze the governance of BTQ programs based on the integration of religious habituation in shaping the graduate profile of Madrasah Ibtidaiyah. The study employs a qualitative case study approach conducted at MI Al-Ishlah Kuala Jambi, involving teachers, school administrators, and students selected through purposive sampling. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that effective BTQ program governance is achieved through the integration of structured planning, routine implementation embedded in daily religious practices, and continuous, although not fully standardized, evaluation. This integration fosters not only students’ Qur’anic literacy skills but also strengthens their religious character and discipline. The study concludes that the success of BTQ programs lies in the alignment between managerial processes and religious habituation, resulting in a holistic graduate profile. Strengthening evaluation systems and expanding family involvement are recommended to enhance program sustainability and impact.